Otosclerosis: comparison of complex-motion tomography and computed tomography. - Chintapalli, K; Unger, J M; Shaffer, K; Millen, S J (American Journal of Neuroradiology, 1985)
A prospective computed tomographic and complex-motion tomographic evaluation was performed in 18 suspected or proven cases of otosclerosis. Although there was good agreement between both methods, there was no greater diagnostic accuracy with computed tomography. However, computed tomography demonstrated the changes better than complex-motion tomography.